Identification of HubHLH family and key role of HubHLH159 in betalain biosynthesis by activating the transcription of HuADH1, HuCYP76AD1-1, and HuDODA1 in pitaya. (March 2023) - Chen, Jiayi; Xie, Fangfang; Shah, Kamran; Chen, Canbin; Zeng, Jianmei; Chen, Jiaxuan; Zhang, Zhike; Zhao, Jietang; Hu, Guibing; Qin, Yonghua
Abstract: Basic helix-loop-helix (bHLH) proteins are dimeric transcription factors (TFs) involved in various plant physiological and biological processes. Despite this, little is known about the molecular properties and roles of bHLH TFs in pitaya betalain biosynthesis. Here we report the identification of 165 HubHLH genes in H. undantus genome, their chromosomal distribution, physiochemical characteristics, conserved motifs, gene structure, phylogeny and synteny of HubHLH genes. Based on phylogenetic relationship analysis, the 165 HubHLHs were divided into 26 subfamilies and unequally distributed on the 11 chromosomes of pitaya. Based on the pitaya transcriptome data, a candidate gene HubHLH159 was obtained, and the real-time quantitative PCR analysis confirmed that HubHLH159 showed a high expression level in 'Guanhuahong' pitaya (red-pulp) at mature stage, indicating its role in betalain biosynthesis. HubHLH159 is a Group II protein and contains a bHLH domain. It is a nuclear protein with transcriptional activation activity. Dual luciferase reporter assays and virus-induced gene silencing (VIGS) experiments showed that HubHLH159 promotes betalain biosynthesis by activating the expression of HuADH1, HuCYP76AD1–1, and HuDODA1 . The results of the present study lay a new theoretical reference for the regulation of pitaya betalain biosynthesis and also provides as essential basis for the future analysis of the functions of HubHLH gene family. Highlights: Totally 165 HubHLH genes unevenly distributed on the 11 chromosomes of pitaya were identified. A novel bHLH transcription factor HubHLH159 associated with pitaya betalain biosynthesis was obtained. HubHLH159 promotes betalain biosynthesis by activating the expression of HuADH1, HuCYP76AD1-1, and HuDODA1 .